An Investigation into the Challenges of Writing in the EFL Classroom from the Perspectives of University Students at the English Department, Faculty of Languages, Benghazi University (Comprehensive Journal of Science, 2026)
Writing is often one of the hardest skills for learners of English as a foreign language to develop. This paper looks at the difficulties university students encounter when writing academically in English. It focuses on second-semester students at the Faculty of Languages, University of Benghazi, and draws on data from a Likert-scale questionnaire completed by 63 students. The findings point to recurring problems with grammar, vocabulary, and organisation, along with low confidence in writing. Based on these results, the paper offers practical suggestions for improving instruction and supporting student writers.
Keywords: academic writing, writing difficulties, instructional practices, EFL, Benghazi University.